SketchUp 2014 For Dummies. - Chopra, Aidan (--For dummies., 2014)
Start building your 3D model today with a comprehensive guide to SketchUp 2014 SketchUp 2014 For Dummies is a user-friendly guide to creating 3D models, adding textures, creating animated walkthroughs, and more, using one of the most popular 3D modeling programs on the market. Fully updated to align with the release of SketchUp, the book guides you through the interface, tools, techniques, and tricks in SketchUp and SketchUp Pro, on both Windows and Mac platforms. Written for designers with no prior 3D modeling experience, the book provides beginner- to intermediate-leve.